Subthalamic Stimulation Inhibits Bladder Contraction by Modulating the Local Field Potential and Catecholamine Level of the Medial Prefrontal Cortex - Yamamoto, Tatsuya; Sakakibara, Ryuji; Uchiyama, Tomoyuki; Kuwabara, Satoshi (Frontiers in Neuroscience, 2020)
Aims: The patients with Parkinson’s disease (PD) present with lower urinary tract symptoms (LUTS), but the efficacy of subthalamic nucleus deep brain stimulation (STN-DBS) on LUTS is unknown. The medial prefrontal cortex (mPFC) is a known higher micturition center which are modulated by STN-DBS. We aim to clarify STN-DBS-related changes in the neuronal activity of the mPFC in terms of bladder contraction, using normal and PD rats. Methods: Experiments were performed under urethane anesthesia in normal and 6-hydroxydopamine hemi-lesioned PD rats. STN-DBS was applied to the left STN, with simultaneous monitoring of bladder contractions. Local field potential (LFP) of mPFC was recorded before, during, and after STN-DBS (n = 6: normal rats, n = 6: PD rats). Extracellular fluid was collected from the mPFC before, during, and after STN-DBS (n = 5: normal rats, n = 6: PD rats). Results: STN-DBS significantly increased bladder inter-contraction interval. STN-DBS significantly decreased mPFC alpha power in normal rat and increased alpha power in PD rat. The mPFC levels of levodopa, dopamine, serotonin, and their metabolites were significantly decreased during and after STN-DBS in PD rats, whereas the levels of serotonin and its metabolites and homovanillic acid (HVA) were significantly decreased after STN-DBS in normal rats. Conclusion: STN-DBS increased bladder inter-contraction intervals in both normal and PD rats probably through changes in neural activity, as evaluated by the alpha power and catecholamine levels in mPFC. The effect of STN-DBS on the levels of catecholamine in mPFC was different between normal and PD rats.